Higher antioxidant activity in decoction than raw fruit parts of Lagenaria siceraria (Mol.) Standley as determined by pulse radiolysis - Joshi, Padmashree; Kulkarni, Mukula; Joag, Sushama (Free Radicals and Antioxidants)
Antioxidant activity of decoctions and fresh juice samples of raw fruit parts of Lagenaria siceraria (Mol.) Standely, (L.S.), viz., fruit pulp, whole fruit and fruit skin, has been evaluated in terms of radical scav- enging ability by pulse radiolysis method and phenolic content by FolineCiocalteu assay. The decay of ABTS radical anion generated by pulse radiolysis has been monitored in presence of samples. The trend in the radical scavenging ability of six samples recorded in terms of ascorbic acid equivalent (AAE) values (4.650e41.230 AAE mg/g fresh weight) have been found to correlate well with the trends in phenolic content of these samples expressed as gallic acid equivalent (GAE) values (0.417e2.000 GAE mg/g fresh weight). The result also shows that the antioxidant activity of decoctions of all the three fruit parts is higher, apparent from their higher AAE and GAE values than the corresponding fresh juice samples.
Keywords: Radical scavenging activity; FolineCiocalteu reagent; Phenolic content; Bottle gourd; Decoction